Make the Connection : Improve Your Communication at Work and at Home - Adubato, Steve (Rutgers University Press, 2005)
In this collection of compelling and practical essays, Emmy Award-winning broadcaster, newspaper columnist, and motivational speaker Steve Adubato shares concrete tips and tools that will help you connect more effectively at work, at home, under pressure, in leadership roles, and in high-tech environments. From avoiding unnecessary arguments with your spouse to coaching a valuable, yet difficult employee, Adubato's essays delve into the key factors that motivate people to act and respond the way that they do.